2019
DOI: 10.1186/s12199-019-0814-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and presenteeism among healthcare workers in China: the mediating role of organizational commitment

Abstract: Objectives We assessed the role of social support in presenteeism by examining organizational commitment among Chinese healthcare workers. Methods One thousand four hundred thirty-four healthcare workers from 6 hospitals in 4 Chinese cities completed a questionnaire measuring presenteeism, social support, and organizational commitment. With organizational commitment as the mediator, regression analyses and structural equation modeling were used to test the model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 47 publications
4
43
0
3
Order By: Relevance
“…37 A number of recent studies on health workers in China also supported the ndings about the signi cant indirect effects between supervisor support and presenteeism, and between coworker support and presenteeism. 38,39 In these studies, it was found that coworker support had a signi cant inverse effect on presenteeism, and collectively with supervisor support could improve organizational commitment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…37 A number of recent studies on health workers in China also supported the ndings about the signi cant indirect effects between supervisor support and presenteeism, and between coworker support and presenteeism. 38,39 In these studies, it was found that coworker support had a signi cant inverse effect on presenteeism, and collectively with supervisor support could improve organizational commitment.…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of evidence suggests that social support may have a role to play in alleviating presenteeism although indirectly. [37][38][39] A study in 2015 that used Japanese IT employees as study objects suggested that presenteeism could be predicted by a lack of workplace social support. 37 A number of recent studies on health workers in China also supported the ndings about the signi cant indirect effects between supervisor support and presenteeism, and between coworker support and presenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…37 A number of recent studies on health workers in China also supported the findings about the significant indirect effects between supervisor support and presenteeism, and between coworker support and presenteeism. 38,39 In these studies, it was found that coworker support had a significant inverse effect on presenteeism, and collectively with supervisor support could improve organizational commitment.…”
Section: Introductionmentioning
confidence: 98%
“…37 A number of recent studies on health workers in China also supported the findings about the significant indirect effects between supervisor support and presenteeism, and between coworker support and presenteeism. 38,39 In these studies, it was found that coworker support had a significant inverse effect on presenteeism, and collectively with supervisor support could improve organizational commitment.…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of evidence suggests that social support may have a role to play in alleviating presenteeism although indirectly. [37][38][39] A study in 2015 that used Japanese IT employees as study objects suggested that presenteeism could be predicted by a lack of workplace social support. 37 A number of recent studies on health workers in China also supported the findings about the significant indirect effects between supervisor support and presenteeism, and between coworker support and presenteeism.…”
Section: Introductionmentioning
confidence: 99%